MODERATING EFFECT OF AGING POPULATION ON THE RELATIONSHIP BETWEEN VIRTUAL TEAM COHESIVENESS AND TEAM PERFORMANCE - Mohd Yusof, Ahmad Nizam (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Digital communication has made it easier for people to work together by breaking down organisational borders and allowing virtual teams to form. These teams, made up of people who live in different places, rely on computer-mediated communication, which makes it harder to build trust, stay together, and work together. This study evaluates the impact of virtual team cohesiveness on team performance and explores the moderating influence of ageing demographic cohorts (Baby Boomers, Generation X, Generation Y). We used Structural Equation Modelling (SEM) to look at data from 500 Malaysian academic personnel who were teaching online. The findings demonstrate that cohesiveness, trust, and the use of information and communication technology (ICT) substantially affect performance. Additionally, generational differences influence the cohesiveness–performance relationship: younger groups gain more from cohesive interactions, whereas older groups depend more on trust and regulated communication. The results underscore age-sensitive approaches for overseeing. virtual teams.